Antonio da Silva Jardim na história do ensino de leitura e escrita no Brasil - Pasquim, Franciele Ruiz (Editora Oficina Universitária, 2022)
This beautiful little book deals with a chapter in the history of literacy in Brazil, or rather the story of the immense struggle for literacy in Brazil. The core of Franciele Ruiz Pasquim's object is the remarkable lecture given by Silva Jardim, in 1884, to enter the Normal School of São Paulo. The conference was held in a context of social and institutional crisis in the country, in a context of broad ideological debate, with the production of new ideas, such as the incorporation of positivism professed by Silva Jardim. Silva Jardim, an educator, is a little-known facet of this militant intellectual, best known for his fight for the establishment of the Republic and the abolition of slave labor. But it is important to note, as Franciele Ruiz Pasquim does, that the educator is an important part of the republican intellectual. The literacy of an entire people, as invested by Silva Jardim, would only be possible with the removal of obstacles that represented slavery and the monarchy. In the same way, generalized literacy would be a program and a condition for the existence of a prosperous Republic. It is regrettable that Brazil, which was lagging behind in terms of literacy when Silva Jardim made his statement, has remained lagging behind for much longer. Sixty years later, in 1944, Astrojildo Pereira still insisted that the main task of the intelligentsia was the literacy of the Brazilian people. In fact, literacy, education and culture for workers were never of interest to the classes that dominate Brazil for their exclusive benefit. MARCOS TADEU DEL ROIO